Nowoczesna organizacja biblioteki akademickiej na przykładzie Biblioteki Uniwersytetu Wileńskiego - Dąbrowska, Ewa (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The article presents the Library of Vilnius University, one of the oldest and most modern libraries in Europe. Its modernity is reflected in the types of services, the organization of the library space and work. The library’s policy is based on the philosophy associated with the mission of Vilnius University. It implies creating an attractive environment, supporting the search for information, study, research and cultural education. The main task of the Library is, therefore, to support and develop scientific communication. A large emphasis is placed on the services for the university environment, both for students and academic staff. Information technologies are used at a high level, and the use of digital materials now exceeds the use of traditional ones. The thing that draws attention is the organizational structure of the library based on tasks and services offered to users. The library is characterized by the rational use of staff and collections while meeting the needs of users to the maximum. It is focused on self-service: a large part of the collection is easily accessible, there is also a self-service store room of course books. The library houses space for individual and collective work, computer laboratories, seminar and conference rooms. While organizing the library space, the following important issues were taken into account: relaxation and easier interpersonal contacts; and therefore there are a number of zones of a quiet or loud rest. Part of the library is open 24 hours a day, 7 days a week. In addition, the library provides consulting services through subject specialists and departments which deal with scientific information and communication. The library has also developed a system of internal and external communication. The modernity of the library is reflected not so much in the use of the latest technology, but in modern management methods in all aspects of its operation.